Peningkatan Keamanan Router Mikrotik Terhadap Serangan Denial of Service (DoS) - Jaya, Budi; Yunus, Yuhandri; Sumijan, Sumijan (Jurnal Sistim Informasi dan Teknologi, 2020)
Denial of Service (DoS) attacks are one of the most common attacks on website, networks, routers and servers, including on router mikrotik. A DoS attack aims to render a network router unable to service requests from authorized users. The result will disrupt the operational activities of the organization and cause material and non-material losses. In this study, a simulation and analysis of DoS attacks using the Live Forensics method were carried out and the router security enhancement from rectangular software and hardware. From the research results obtained digital evidence of DoS attacks in the form of IP addresses and attacker activity logs. In addition, the increase in router security in terms of software by using Firewall Filter and Firewall Raw has proven effective in preventing attacks. While improving router security in terms of hardware by setting a reset button on the router and firewall devices is also very necessary so that the router can avoid physical attacks by irresponsible persons.